INFLUENCE OF CHORD LENGTH AND LOAD DISTRIBUTION MODIFICATION ON THE SOUND EMISSION AND EFFICIENCY OF A BENCHMARK FAN - Benz, Julian; Czwielong, Felix; Renz, Andreas; Ocker, Christof; Sedlmajer, Michael; Merkel, Markus; Schoder, Stefan; Becker, Stefan (Proceedings of Forum Acusticum, 2023)
The design parameters of axial fans, such as load distribution over the blade, chord length and the angle of attack, significantly influence the resulting aerodynamic and aeroacoustic properties of the fans. Based on an international benchmark fan, its design parameters were modified and two additional fans were created. In the process, all three fans had the same specific load, but in one case the chord length of the fan was varied and in the second case an additionally modified load distribution was applied. The modified load distribution is based on Prandtl's idea that a bell-shaped load distribution has the lowest induced drag on aircraft wings by reducing the wing tip vortex. The numerical investigations demonstrated that this reduction can be also achieved on axial fans leading to increased aerodynamic efficiency. By using the Lighthill analogy, a decrease in the sound emission of the fan could be found. In addition, the modification with the increased chord length exhibits improved aerodynamic and acoustic properties compared to the benchmark fan.
CRIS-Team Scopus Importer:2024-12-16
Keywords: axial fan; CAA; CFD; chord length; load distribution